Mandatory reporting and the retaliation factor. (January 2023) - Sippel, Franne; Meister, Karyl L.; Miller, Pamela J.; Howard, Jeff N.; Can, Ahmet; Bowden, Theresa; Garlick, Andrea
Abstract: Despite state and federal immunity protections, mandated reporters (MRs) of child maltreatment often experience retaliation from alleged perpetrators, employers, or other entities. Existing research demonstrates a correlation between experiencing retaliation and failing to report incidents of future maltreatment. Retaliation may include adverse employment actions, releasing the MRs' identity, civil lawsuits, board complaints, and harassment. This study examines the impact of experienced/witnessed retaliation, fear of retaliation, and professional training on MRs' willingness to report maltreatment, accept maltreatment cases, and testify in court. A self-administered survey sampled 619 MRs from varying professions throughout the United States and found (27.1%) experienced retaliation, though (14.9%) of those did not indicate retaliation type experienced. The most common forms included harassment (73.8%) and releasing the MRs' identity (30.4%). Experienced retaliation resulted in MRs being less willing to report maltreatment and testify in court. Witnessed retaliation resulted in MRs being less likely to report abuse and accept certain maltreatment cases.